2021
DOI: 10.1159/000518065
|View full text |Cite
|
Sign up to set email alerts
|

Improved Dialysis Removal of Protein-Bound Uraemic Toxins with a Combined Displacement and Adsorption Technique

Abstract: <b><i>Introduction:</i></b> Protein-bound uraemic toxins (PBUTs) are poorly removed by conventional dialytic techniques, given their high plasma protein binding, and thus low, free (dialysable) plasma concentration. Here, we evaluated and compared PBUTs removal among conventional haemodialysis (HD), adsorption-based HD, displacement-based HD, and their 2 combinations both in vitro and in vivo. <b><i>Methods:</i></b> The removal of PBUTs, including 3-carboxy-4-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
(109 reference statements)
0
7
0
Order By: Relevance
“…In silico analysis informed us that competitive binding during HD significantly outperforms other state-of-the-art dialysis therapies, namely pre-and postdilution hemodiafiltration and ideal membrane adsorption (Figure 6) [22]. These in silico findings are qualitatively validated by Shi et al 2021, who compared binding competition and adsorption (by albumin dialysis) in pre-clinical uremic rat models and observed that binding competition outperformed adsorption [20].…”
Section: In Silico Evidencementioning
confidence: 60%
See 1 more Smart Citation
“…In silico analysis informed us that competitive binding during HD significantly outperforms other state-of-the-art dialysis therapies, namely pre-and postdilution hemodiafiltration and ideal membrane adsorption (Figure 6) [22]. These in silico findings are qualitatively validated by Shi et al 2021, who compared binding competition and adsorption (by albumin dialysis) in pre-clinical uremic rat models and observed that binding competition outperformed adsorption [20].…”
Section: In Silico Evidencementioning
confidence: 60%
“…Binding competition outperformed albumin dialysis and improved IS and pCS removal by approximately 10-fold in comparison to conventional 4 h HD. Notably, combining binding competition and albumin dialysis further improved the removal of putative PBUTs [20]. This study indirectly underscores the fact that protein binding is the primary resistance for PBUTs removal.…”
Section: Clinical Evidencementioning
confidence: 60%
“…The same rationale applies to protein-bound uremic toxins. An in vitro model demonstrated that the removal of indoxyl sulfate, p-cresyl sulfate, and hippuric acid was higher with a dialysate containing albumin when compared to standard bicarbonate dialysate [72]. Clinical trials with this strategy are still lacking.…”
Section: Adsorptionmentioning
confidence: 99%
“…Second, we propose an approach that combines displacement of CMPF using an exogenous binding competitor to increase its free fraction followed by adsorption (Figure 4C). 16 Previous clinical proof-of-concept studies have demonstrated the utility of the displacer concept to enhance the dialytic removal of protein-bound uremic solutes. 17 Third, albumin dialysis, a method used primarily in patients with liver failure to remove .…”
Section: Jedi1 Jedi1mentioning
confidence: 99%